2019
DOI: 10.1152/ajpendo.00443.2018
|View full text |Cite
|
Sign up to set email alerts
|

Intact innervation is essential for diet-induced recruitment of brown adipose tissue

Abstract: The possibility that recruitment and activation of brown adipose tissue (BAT) thermogenesis could be beneficial for curtailing obesity development in humans prompts a need for a better understanding of the control of these processes [that are often referred to collectively as diet-induced thermogenesis (DIT)]. Dietary conditions are associated with large changes in blood-borne factors that could be responsible for BAT recruitment, but BAT is also innervated by the sympathetic nervous system. To examine the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 91 publications
9
58
1
Order By: Relevance
“…Currently, an ablation of nerve bundles of bilateral BAT was used to abolish the function of BAT in vivo. In consistence with previous studies (48,49,61), the surgical denervation was confirmed by the significant elimination of TH in BAT in the current study. We found that whitening occurred in denervated of BAT as evidenced by the uniocular morphology and decreased levels of UCP1 protein.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Currently, an ablation of nerve bundles of bilateral BAT was used to abolish the function of BAT in vivo. In consistence with previous studies (48,49,61), the surgical denervation was confirmed by the significant elimination of TH in BAT in the current study. We found that whitening occurred in denervated of BAT as evidenced by the uniocular morphology and decreased levels of UCP1 protein.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study has reported that bilateral denervation of BAT can promote sWAT browning at thermoneutrality (48). However, A more recent study showed that no browning of sWAT was detectable in BAT-denervated mice (61). Similarly, in BATdenervated and BAT-removal mice at room temperature, we did not achieve significant evidence for browning of sWAT.…”
Section: Discussioncontrasting
confidence: 84%
“…Different stimuli, like, e.g., abovementioned exposure to cold, lead to increased noradrenaline release and subsequent stimulation of various subtypes of β-adrenergic receptors (ADRBs), leading to the proliferation of brown adipocytes and activation of lipolysis and/or of thermogenesis. ADRB3 is the primary receptor involved in pathways related to adaptive thermogenesis in brown or beige adipocytes [ 34 ].…”
Section: Adipose Tissue Browningmentioning
confidence: 99%
“…However, during disease states such as obesity, BMI can be above 30 kg/m 2 . WAT serves as the main energy store for the body, while brown adipose tissue (BAT) dissipates energy into heat via non-shivering thermogenesis (6)(7)(8).…”
Section: Brown/beige Adipose Tissue Biology Brown/beige Adipose Tissuementioning
confidence: 99%